EFFECT OF PEPPERMINT SUPPLEMENTATION AS POWDER OR EXTRACT ON BROILER PERFORMANCE, SERUM BIOCHEMICAL CONTENT AND GUT HEALTH UNDER E COLI CHALLENGE - & Sadeq, Hasan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of this study was to evaluate the efficacy of different levels of peppermint (Mentha piperita) on broiler performance, jejunum morphology, organs percentage and serum biochemical content.  A total of 576-day old ross 308 chickens was divided randomly into 12 treatments with 4 replicates pen per treatment and 12 birds each pen. Treatments were arranged in a 2 × 6 factorial arrangement of treatments was employed. Factors were challenge, - or +; control, antibiotic, 0.5 % peppermint in feed, 1% peppermint in feed, 0.5% peppermint in water and 1% peppermint in water. The result of study was showed that the peppermint supplementation was significant effect on feed intake, feed conversion ratio and it has effect on body weight at day 24 and 35. The peppermint supplementation either in feed and water at 24 day had a significant effect on jejunum muscle thickness and villus/ crypt ratio while not effect on villus height and crypt depth. In conclusion, supplementation of peppermint has positive effect on broiler performance and gut morphology.